Sun Sailing Polar Orbiting Telescope (SunSPOT): A solar polar imaging mission design. Issue 2 (15th July 2022) - Probst, A.; Anderson, T.; Farrish, A.O.; Kjellstrand, C.B.; Newheart, A.M.; Thaller, S.A.; Young, S.A.Q.; Rankin, K.; Akhavan-Tafti, M.; Chartier, A.; Chintzoglou, G.; Duncan, J.; et al.
Abstract: Although the Sun has been a focus of space-based research for several decades, there are still many open questions. One severe gap in solar physics knowledge is the lack of detailed, long-term observations of the solar polar regions to explore the origins of the Sun's magnetism and other connected phenomena. To fill this gap, this paper presents a feasibility study of a mission concept for a solar polar orbiting imaging mission called the Sun Sailing Polar Orbiting Telescope (SunSPOT) . SunSPOT utilizes a doppler magnetograph instrument to observe the polar magnetic structure and a large deployable solar sail to reach high inclination orbit. The mission concept is derived from two science objectives investigating the formation of solar active regions and the solar dynamo. These objectives are aligned with the science goals formulated by the National Research Council (NRC) in the 2013 Decadal Survey in Solar and Space Physics and their science closure is shown in the Science Traceability Matrix . The mission and spacecraft design are explained, including a cost and risk analysis, with a special focus on the requirements and risks of the solar sail propulsion system. While the solar sail presents a significant design challenge and financial risk to this and other proposed solar polar missions, it is a necessity to achieve the orbit required for closure of decadal science goals. Although originally conceived of as a Discovery-class mission fitting within a $600 M budget, the solar sail pushes the cost beyond this threshold. The work presented here is the outcome of the NASA Heliophysics Mission Design School (HMDS) 2020 hosted by the NASA Jet Propulsion Laboratory.